Effect of Glass Ionomer Filler Size on Fluoride Release, Antiplaque Properties, and Abrasive Effects of Toothpaste - Behnaz Vahidi; Homayoon Alaghehmand; Hamed Tashakkorian; Seyedali Seyedmajidi; Maryam Ghasempour (Clinical and Experimental Dental Research)
ABSTRACT Objectives This study aimed to assess the impact of incorporating glass ionomer fillers of varying sizes on fluoride release, antiplaque properties, and the abrasive effects of toothpaste. Materials and Methods In this laboratory study, three toothpaste samples containing glass ionomer filler particles (0.5, 5 µm, and a hybrid combination of equal proportions of both fillers) were tested, along with a base toothpaste without fillers or fluoride and a commercial toothpaste (Colgate Total) as controls. Fluoride release was measured using a fluoride ion‐selective electrode. Antiplaque properties were assessed by evaluating the effect of toothpaste on cultured saliva in tissue culture plates, with optical density measured using an ELISA reader. Abrasive effects were analyzed by changes in enamel thickness of bovine teeth using a three‐body wear test. Data were analyzed with ANOVA and Tukey's tests in SPSS software at a 0.05 significance level. Results Toothpaste containing 0.5 µm fillers showed the highest fluoride release, whereas the lowest release was associated with 5 µm fillers. All formulations demonstrated antiplaque activity, though differences among filler‐containing toothpastes were not statistically significant (p > 0.05). Enamel abrasion differed significantly among the samples (p < 0.001), with the greatest abrasion observed for toothpaste containing 5 µm fillers and the least abrasion observed for 0.5 µm fillers. Conclusions Incorporating glass ionomer fillers into toothpaste formulations provides fluoride release and antiplaque effects comparable to those of commercial toothpaste. Smaller filler sizes enhance fluoride release and reduce abrasiveness, though filler size does not significantly influence antiplaque efficacy.